Intrinsic and extrinsic regulation of type III secretion gene expression in Pseudomonas aeruginosa - Diaz, Manisha R.; King, Jessica M.; Yahr, Timothy L. (Frontiers in Microbiology, 2011)
Pseudomonas aeruginosa is an opportunistic pathogen that is particularly problematic in the healthcare setting where it is a frequent cause of pneumonia, bloodstream, and urinary tract infections. An important determinant of P. aeruginosa virulence is a type III secretion system (T3SS). T3SS-dependent intoxication is a complex process that minimally requires binding of P. aeruginosa to host cells, injection of the cytotoxic effector proteins through the host cell plasma membrane, and induction of T3SS gene expression. The latter process, referred to as contact-dependent expression, involves a well-characterized regulatory cascade that activates T3SS gene expression in response to host cell contact. Although host cell contact is a primary activating signal for T3SS gene expression, the involvement of multiple membrane-bound regulatory systems indicates that additional environmental signals also play a role in controlling expression of the T3SS. These regulatory systems coordinate T3SS gene expression with many other cellular activities including motility, mucoidy, polysaccharide production, and biofilm formation. The signals to which the organism responds are poorly understood but many seem to be coupled to the metabolic state of the cell and integrated within a master circuit that assimilates informational signals from endogenous and exogenous sources. Herein we review progress towards unraveling this complex circuitry, provide analysis of the current knowledge gaps, and highlight potential areas for future studies. Complete understanding of the regulatory networks that control T3SS gene expression will maximize opportunities for the development of strategies to treat P. aeruginosa infections.